SPE Western Regional Meeting 2018
DOI: 10.2118/190039-ms
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Toxicity Effects of Oil Field Chemicals Using Adaptive Genetic Neuro-Fuzzy Inference Systems

Abstract: Chemicals are used in various stages of oil production such Drilling (Drilling fluids, cementing, completion and workover fluids), Production, Stimulation and Enhanced Oil Recovery. Many research studies have shown these oil field chemicals have toxic effects on the environment. The oilfield chemicals include various additives for drilling/cementing and work-over such as Fluid loss additives, rheology modifiers, Viscosifiers, Emulsifiers, Biocides, Surfactants, Packer fluid corrosion inhibitors. Toxicity tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Okogbue et al [12] carried out an assessment to ascertain the possible pollution from produced water discharges on offshore waters in the Niger Delta area of Nigeria. From their findings, they concluded that pollutant parameters (like heavy metals and the hydrocarbon constituents) in the produced water have the capacity to alter the composition and quality of seawater and in turn pose severe threat to the Niger Delta aquatic environment [13].…”
Section: Introductionmentioning
confidence: 99%
“…Okogbue et al [12] carried out an assessment to ascertain the possible pollution from produced water discharges on offshore waters in the Niger Delta area of Nigeria. From their findings, they concluded that pollutant parameters (like heavy metals and the hydrocarbon constituents) in the produced water have the capacity to alter the composition and quality of seawater and in turn pose severe threat to the Niger Delta aquatic environment [13].…”
Section: Introductionmentioning
confidence: 99%